Effect of temperature on microstructures and mechanical properties of medium‐carbon low‐alloy steel by caliber rolling. Issue 9 (13th September 2022) - Yang, B.; Liu, B.X.; Zhang, B.Y.; Dong, M.C.; Chen, C.X.; Ji, P.G.; Li, Z.Y.; Yin, F.X.
Abstract: The effect of initial heat‐treated conditions on change of mechanical properties and microstructure evolution was investigated by caliber rolling of medium carbon alloy steel (ASTM 5140). Initial samples with two different kinds of microstructures of pearlite‐ferrite and martensite were prepared, and then caliber rolling was conducted at 550 °C, 600 °C, 650 °C, respectively. It was found that the caliber rolling provides better strength‐ductility balance and impact properties, when the rolling temperature is at 550 °C, the ultimate tensile strength of quenched steel can reach 1.3 GPa, and low‐temperature impact energy of 140 J at −80 °C. In a word, the improvement of mechanical properties is attributed to the ultrafine elongated grain structures, dispersed nano‐size carbides, and formation of distinct chromium segregation bands, furthermore, delamination crack is an effective measure to improve impact energy. Abstract : In this paper, the ultrafine elongated grain, strong fibrous structure and carbide laminated distribution along the rolling direction are prepared by temperature‐controlled pass rolling technology, which can greatly improve its yield strength and low temperature impact resistance, etc., and has a wide application prospect.